2006
DOI: 10.1038/sj.jes.7500509
|View full text |Cite
|
Sign up to set email alerts
|

The effects of recall errors and of selection bias in epidemiologic studies of mobile phone use and cancer risk

Abstract: This paper examines the effects of systematic and random errors in recall and of selection bias in case-control studies of mobile phone use and cancer. These sensitivity analyses are based on Monte-Carlo computer simulations and were carried out within the INTERPHONE Study, an international collaborative case-control study in 13 countries. Recall error scenarios simulated plausible values of random and systematic, non-differential and differential recall errors in amount of mobile phone use reported by study s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
1
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 41 publications
1
65
1
1
Order By: Relevance
“…If there is a real association between mobile phone use and brain tumour risk, the nondifferential random errors that dominate this validation study would be expected to bias risk estimates towards the null (no effect), and increase their uncertainty, making it more likely that real associations would not be detected (Armstrong, 1990;Armstrong et al, 1992;Vrijheid et al, 2006b). However, such errors do not normally induce spurious associations if there is no true association between exposure and outcome (Armstrong, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If there is a real association between mobile phone use and brain tumour risk, the nondifferential random errors that dominate this validation study would be expected to bias risk estimates towards the null (no effect), and increase their uncertainty, making it more likely that real associations would not be detected (Armstrong, 1990;Armstrong et al, 1992;Vrijheid et al, 2006b). However, such errors do not normally induce spurious associations if there is no true association between exposure and outcome (Armstrong, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Differential errors observed in longer term phone use could induce positive bias. We have observed in a simulation study that, in the presence of large random errors, systematic errors made very little additional impact on assumed risk estimates for continuous exposure indices (cumulative hours of phone use), even when relatively extreme systematic errors were modelled and when the systematic errors simulated differed between cases and controls (Vrijheid et al, 2006b). …”
Section: Discussionmentioning
confidence: 99%
“…In that study, however, self-reported data on the use of mobile phones was used, which is of concern in case-control studies (Vrijheid et al 2006). …”
Section: Discussionmentioning
confidence: 99%
“…Thus, the design and performance of these studies, using the same core protocol, seem to be biased in certain respects. This has been discussed by others and us elsewhere (4,5,30,31). In a Danish Interphone study it was concluded that the cognitive function in brain tumour cases was affected leading to e.g.…”
Section: A ----------------------------------------------------------mentioning
confidence: 99%
“…Some articles have discussed methodological issues in the Interphone studies (30,31). The actual use of mobile phones was underestimated in light users and overestimated in heavy users.…”
Section: A ----------------------------------------------------------mentioning
confidence: 99%